To solve this integral, we can use integration by parts. The integration by parts formula states:
∫u dv = uv - ∫v du
Let's assign u = x^2 and dv = e^x dx. Then, we can find du and v:
Taking the derivative of u, we get du/dx = 2x. To find v, we integrate dv = e^x dx. The integral of e^x is simply e^x, so v = e^x.
Now, we can apply the integration by parts formula:
∫x^2 e^x dx = x^2 e^x - ∫2x e^x dx
The remaining integral, ∫2x e^x dx, can be solved using integration by parts again. Assigning u = 2x and dv = e^x dx, we find du = 2 dx and v = e^x. Applying the integration by parts formula once more:
∫2x e^x dx = 2x e^x - ∫2 e^x dx
The integral ∫2 e^x dx is simply 2 e^x, so the final result is:
∫x^2 e^x dx = x^2 e^x - 2x e^x + 2 e^x + C
where C is the constant of integration.
For example, if we want to evaluate the integral from 0 to 1, we substitute the limits of integration into the result:
∫[0,1] x^2 e^x dx = (1^2 e^1 - 2(1) e^1 + 2 e^1) - (0^2 e^0 - 2(0) e^0 + 2 e^0)
Simplifying, we obtain:
∫[0,1] x^2 e^x dx = (e - 2e + 2e) - (0 - 0 + 2)
∫[0,1] x^2 e^x dx = e
Therefore, the value of the integral from 0 to 1 is e.
For references and further reading on integration techniques, you may refer to:
I hope this explanation helps! Let me know if you have any further questions.
© 2025 Invastor. All Rights Reserved
User Comments